Empowering Tharu and Bote Women Through Vocational Skills: A Case of Amaltari Homestay - Newpane, Surya Prasad (Journal of Training and Development, 2020)
Tharu and Bote are indigenous groups of Nepal. They have been surviving by using their traditional skills and indigenous knowledge. However, at present, they have gradually started shifting their survival skills for their economic and socio-cultural development. Homestay is one such initiation and women’s role in particular has been vital to this initiation which is usually unnoticed in the society. In connection to this, this paper incorporates the stories of women who uses their vocational skills to run a homestay in their community. For this, a qualitative approach was used and Amaltari homestay which is run by the Tharu and Bote of Nawalparasi was selected as the research site. Several rounds of interactions with owners of the homestay, group discussion with community people and observation were used to collect information. The study found that the women of Tharu and Bote community in Amaltari homestay village have been using their skills in the area of hospitality, cooking traditional foods and crafting bamboo and wooden goods that can be sold to the guests as souvenir. Furthermore, they have been able to keep financial records of their business as well. In this sense, the homestay has significantly contributed to the indigenous practice and has been supportive in uplifting the Tharu and Bote women socially and culturally by using the traditionally learned vocational skills.